Chitosan/sericin blend membranes for adsorption of bovine serum albumin. (4th January 2017) - Du, Jennifer Runhong; Su, Xiao; Feng, Xianshe
Abstract: Chitosan/sericin blend membranes for adsorption of bovine serum albumin (BSA) were investigated. A preliminary screening test was carried out to identify a suitable chitosan/sericin blend ratio. The blend membrane with a chitosan/sericin mass ratio of 4:1 was found to have a maximum adsorption capacity ( qm ) of 25.3 g/m 2, which is 45 % greater than the maximum adsorption capacity of the pure chitosan membrane. The adsorption‐desorption cycle studies showed that the chitosan/sericin blend affinity membrane could be reused, and over 80 % of the original adsorption capacity was retained after regeneration. Compared to other affinity membranes for BSA adsorption, the chitosan/sericin membrane exhibited a significantly high adsorption capacity with a comparable adsorption rate.